Management of anaplastic thyroid cancer and proposed treatment guidelines—A 5‐year case series study. Issue 11 (4th October 2022) - Koda, Kento; Katoh, Mitsuhiko; Yasuhara, Kazuo
Abstract: Background: Anaplastic thyroid cancer is a rare and rapidly progressive cancer with an extremely poor prognosis. Besides surgical control, no clear treatment has been found, mainly due to the small population affected and high mortality rate. Aims: To propose evidence‐based treatment guidelines based on a 5‐year retrospective study of patients with anaplastic thyroid cancer treated at our facility. There have been no clearly defined guidelines for treatment plan for undifferentiated thyroid cancer. Our paper presents a retrospective analysis on the treatment of patients with undifferentiated thyroid cancer at our hospital. Methods and Results: We retrospectively evaluated the data of patients diagnosed with anaplastic thyroid cancer from April 2017 to March 2022. The total number of patients diagnosed and treated was seven. Two of these patients had operable cancer; five were inoperable and treated with lenvatinib or paclitaxel maintenance therapy. The median time from the first visit to death was 3.84 months, and six of the seven patients died before this study started. Three of them had Stage IVB cancer and died due to deterioration of their general condition, including lung metastasis; the other three had Stage IVC cancer and died of suffocation. The survivor had Stage IVB cancer, was treated by surgery combined with chemical radiotherapy, and survived >240 days. Conclusion: Considering the above findings, personalized surgical treatment should be prioritized to prevent suffocation. Especially in Stage IVB cancer, local control can be achieved by surgical and anticancer drug treatment to avoid death from suffocation.